The implementation of a blog-based activity with prospect teachers: constraints and difficulties - Santamaría Urbieta, Alexandra; García Laborda, Jesús (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
The development of the Web 2.0 in recent years has triggered the use of web-based tools like, for instance, blogs as language development and assessment tools (García Laborda, 2013). This article addresses the difficulties that teacher trainees have when they create and manage their own blogs in a fourth-year course on Didactics of the English language. A sample of blogs created by 15 students in the fourth year of a teacher training program for primary school teachers at the University of Alcalá (Spain) was analyzed qualitatively. Finally, a questionnaire was handed out to students to analyze the limitations and benefits of this tool in the classroom. The main conclusion is that the identification of the analysis of difficulty that students present during the implementation and management of a blog will provide suggestions for teachers-to-be and current university teachers in education Degrees.